Pengaruh kinerja keuangan terhadap harga saham, studi kasus pada PT Bank Mandiri (persero) tbk - Lilik Susilo; Bambang Sugeng Dwiyanto (Journal of Tourism and Economic, 2023)
This study aims to analyze the effect of financial performance on stock prices at PT Bank Mandiri (Persero) Tbk for the period 2017-2021. The independent variables used in this study are financial performance, namely Capital Adequacy Ratio (CAR), Return On Assets (ROA), Return On Equity (ROE), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), and Operational Expenditure to Operating Income (BOPO) and Stock Price as the dependent variable. The analytical method used is multiple regression analysis using SPSS 21. The results show that Return On Equity (ROE) partially has a negative and significant effect on stock prices, Operational Expenditures on Operating Income (BOPO) partially has a negative and insignificant effect on stock prices shares, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non Performing Loans (NPL) partially have no effect on stock prices. Meanwhile, the Capital Adequacy Ratio (CAR), Return On Equity (ROE), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), and Operational Spending to Operating Income (BOPO) simultaneously have a significant effect on stock prices. Interactions from the independent variables CAR, ROE, LDR, NPL, and BOPO with a share price of 70.4% and the difference of 29.6% is explained by other factors.